2020
DOI: 10.1093/humupd/dmaa005
|View full text |Cite
|
Sign up to set email alerts
|

The fundamental role of the endocannabinoid system in endometrium and placenta: implications in pathophysiological aspects of uterine and pregnancy disorders

Abstract: BACKGROUND The endocannabinoid system (ECS) consists of the cannabinoid receptors CB1 and CB2, the main endocannabinoids anandamide (AEA) and 2-arachidonoylglycerol (2-AG) and their metabolic enzymes N-acylphosphatidylethanolamine-specific phospholipase D, fatty acid amide hydrolase, diacylglycerol lipase and monoacylglycerol lipase. This system is involved in the modulation of essential physiological processes. Its role in the reproductive system has become significantly important in recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 161 publications
3
66
0
Order By: Relevance
“…Alterations in proliferation and exacerbation of trophoblast apoptosis have been associated with placental-related complications (Huppertz et al 2006, Heazell & Crocker 2008. On the other hand, dysregulation of the endocannabinoid levels might lead to adverse pregnancy outcomes, including impairment of implantation, inhibition of decidualization and compromised placentation (Maia et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in proliferation and exacerbation of trophoblast apoptosis have been associated with placental-related complications (Huppertz et al 2006, Heazell & Crocker 2008. On the other hand, dysregulation of the endocannabinoid levels might lead to adverse pregnancy outcomes, including impairment of implantation, inhibition of decidualization and compromised placentation (Maia et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In women with endometriosis, there is a significant increase in plasmatic AEA and 2-AG levels. High AEA levels have also been shown to be related to failure in the in vitro fertilization embryo transfer and spontaneous miscarriage, while women with preeclampsia exhibit reduced levels of AEA ( Maia et al 2020 ). Moreover, we previously demonstrated that AEA and 2-AG impair the synthesis of proteins and hormones by the human syncytiotrophoblast ( Costa et al 2015 a , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, growing evidence suggests that the ECS is a part of the diverse mechanisms that regulate the complexity of events that occur in the early stages of pregnancy, and especially within the placenta [ 51 ]. The first trimester trophoblast contains transcripts for both CB 1 and CB 2 [ 52 ], and their expression is important for the continuation of normal pregnancy [ 48 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, they play roles that include oocyte production [ 45 , 59 , 96 , 97 , 98 ], oviductal transport [ 98 , 99 , 100 ], and blastocyst maturity and implantation [ 101 ], as well as in preparing the endometrium for implantation [ 47 , 102 , 103 , 104 , 105 ]. When the ECS is dysfunctional or interfered with by, for example, cannabinoids [ 106 , 107 ], human fertility may be impaired (reviewed in [ 12 , 101 , 108 , 109 ]) and there may be associated reproductive-tissue-dependent pathologies, such as endometriosis, miscarriage, ectopic pregnancy, or pre-eclampsia [ 51 , 101 , 108 , 110 , 111 , 112 ]. Two recent reviews [ 12 , 38 ] on the ECS in the female reproductive tract summarise what is known on this topic, but crucially, these omit some important details on the main ECS components in gynaecological cancers, which we hope to address in this review (see Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation